Toxicity of synthetic insecticides on third instar larvae of Chrysoperla nipponensis (Neuroptera : Chrysopidae) - Jaliludin, Nadiah (2017)
Green lacewing Chrysoperla niponensis is well known as insect predator of pests in the field crop and widely used as biological control agent. Usually an adult feeds on nectar, pollen and sugar excretions. The larvae are considered as active worker and having huge appetite to feed on aphids, red spider mites, thrips, mealybugs and whiteflies. The intensive use of insecticides to control the pest could reduce the number of biological control agents through residual contact with insecticides. Therefore, the purpose of this study was to evaluate toxicity of cypermethrin and spinosad and to identify the most toxic insecticide against the larvae of C. nipponensis. The insecticides that had been used are cypermethrin and spinosad. The experiment was conducted by using leaf-dip bioassay method. The mortality was recorded after 24, 48, 72, 96 and 120 hours and the results were subjected to probit analysis and ANOVA with means separation by Tukey. The most toxic insecticide against third instar larvae was obtained from cypermethrin with LC50 30.28 ppm while the less toxic was examined from spinosad with LC50 182.23 ppm.